Telephone-delivered collaborative care for post-CABG depression is more effective than usual care for improving quality of life related to mental health. Issue 2 (1st May 2010) - Gallagher, Robyn
Abstract : Commentary on: Rollman BL Belnap BH LeMenager MS . Telephone-delivered collaborative care for treating post-CABG depression: a randomized controlled trial . JAMA 2009 ;302 :2095 –103 .